2005
DOI: 10.1097/01.ogx.0000154420.15550.89
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Association Between Preterm Birth and Early Periodontitis: Pilot Study

Abstract: Mexican Americans are the fastest-growing minority group in the United States, and their incidence of low-birthweight (LBW) infants (less than 2500 g) reportedly is higher than for Mexican-born women. The investigators carried out a population-based study of Illinois birth certificates for singleton Mexican-American infants having Mexican-born mothers for the years 1989-1991. The goal was to determine whether the duration of generational resident in the United States correlates with pregnancy outcomes. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 0 publications
2
33
1
Order By: Relevance
“…A history of previous preterm birth was controlled in only five studies [27-29, 33, 39], in seven studies it was not reported [30-32, 35, 36, 38, 42] while five studies found a significant higher incidence of adverse pregnancy outcomes in women with previous preterm birth [34,37,40,41,43]. Statistically significant differences between study groups were reported considering marital status in four studies [29,32,39,43], educational level in three studies [32,37,38], parity in one study [37], history of abortion in one study [37], smoking status in five studies [31,32,35,36,38], and alcohol misuse in one study [31].…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…A history of previous preterm birth was controlled in only five studies [27-29, 33, 39], in seven studies it was not reported [30-32, 35, 36, 38, 42] while five studies found a significant higher incidence of adverse pregnancy outcomes in women with previous preterm birth [34,37,40,41,43]. Statistically significant differences between study groups were reported considering marital status in four studies [29,32,39,43], educational level in three studies [32,37,38], parity in one study [37], history of abortion in one study [37], smoking status in five studies [31,32,35,36,38], and alcohol misuse in one study [31].…”
Section: Resultsmentioning
confidence: 78%
“…After title and abstract examination, 392 articles were excluded because not meeting the inclusion criteria. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. A total of 10,148 subjects were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Offenbacher [44] 1996 Case-control PLBW USA, 60% black 124 Offenbacher [17] 2001 Cohort Preterm USA, 50% black 812 Jeffcoat [18] 2001 Cohort Preterm Alabama, USA, 80% black 1313 Dasanayake [31] 2001 Case-control LBW Thailand 110 Romero [45] 2002 Case-control PLBW Venezuela 69 Lopez [46] 2002 Cohort Preterm, LBW, PLBW Chile, low SES 772 Wan [47] 2002 Case-control Preterm Australia 190 Carta [48] 2004 Case-control PLBW Italy 92 Goepfert [43] 2004 Case-control Preterm Alabama, USA 139 Mokeem [49] 2004 Case-control PLBW Saudi Arabia, medium/high SES 90 Radnai [50] 2004 Case-control PLBW Hungary 85 Dortbudak [39] 2005 Cohort PLBW Austria, undergoing amniocentesis at midtrimester 36 Jarjoura [30] 2005 Case-control Preterm 60% Hispanic 203 Marin [51] 2005 Cohort LBW Brazil, low education 152 Moliterno [52] 2005 Case-control PLBW Brazil, low SES 151 Moreu [53] 2005 Cohort LBW, preterm Spain 96 PLBW, preterm low birth weight; Preterm, preterm birth; LBW, low birth weight; SES socioeconomic status. Periodontal disease, preterm birth, low birth weight, and preterm low birth weight as defined by the author.…”
Section: Number Of Subjectsmentioning
confidence: 99%
“…Probing depth ≥ 4 mm and bleeding on probing (BOP) at ≥ 50% of the teeth were examined together (Lang and Tonetti, 2003;Radnai et al, 2004). The size of the surface in the sulcus where bacteria or their products can invade the tissues is important.…”
mentioning
confidence: 99%